let X be non empty set ; :: thesis: for S being SigmaField of X

for M being sigma_Measure of S holds L-1-Space M = Lp-Space (M,1)

let S be SigmaField of X; :: thesis: for M being sigma_Measure of S holds L-1-Space M = Lp-Space (M,1)

let M be sigma_Measure of S; :: thesis: L-1-Space M = Lp-Space (M,1)

Pre-L-Space M = Pre-Lp-Space (M,1) by Th75;

hence L-1-Space M = Lp-Space (M,1) by Th76; :: thesis: verum

for M being sigma_Measure of S holds L-1-Space M = Lp-Space (M,1)

let S be SigmaField of X; :: thesis: for M being sigma_Measure of S holds L-1-Space M = Lp-Space (M,1)

let M be sigma_Measure of S; :: thesis: L-1-Space M = Lp-Space (M,1)

Pre-L-Space M = Pre-Lp-Space (M,1) by Th75;

hence L-1-Space M = Lp-Space (M,1) by Th76; :: thesis: verum